(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article highlights a new branch of linguistics at the intersection of the disciplines of theolinguistics – religious linguistics, its emergence, the need for religious discourse in societies and its analysis, how relevant is the study of special areas of language in the modern developing world, including theolinguistics. The article, along with a number of scientific studies in this field and multifaceted approaches to them, provides some linguistic units and their theolinguistic analysis presented from the author’s personal research. Additionally, the concept of religious style, its essence, theological colors of texts created in different styles, as well as, the importance of the religious style in linguaculturology and text analysis are illustrated. This new branch of linguistics is comparatively analyzed to what extent and on the basis of which approaches foreign, Russian and Uzbek scientists have studied, and the issues of theological linguistics that have been studied in recent years and are required to be studied are referenced. It is emphasised that there is a great need to study religious linguistics from the perspective of our nationality, our religion, and our national linguistics.